Re-Assessing TOD index in Jakarta Metropolitan Region (JMR) - Herika Muhamad Taki; Mohamed Mahmoud H Maatouk; Emad Mohammed Qurnfulah (Journal of Applied Geospatial Information, 2017)
Transit Oriented Development (TOD) is believed to be able to overcome the issues of urban transport. However, in practice, the current TOD in Jakarta Metropolitan Region (JMR) is still a deficiency in accommodating the needs of transportation movement and not in facilitating services in terms of TOD function. The objective of this paper was to re-assess the service quality of actual TOD in 54 commuter railway stations. The paper performed criteria-indicators and measured a composite TOD index by using Analytical Hierarchy Process (AHP)-multicriteria model, statistics test, and Geographical Information System (GIS) application. TOD index was found that urban areas have a high TOD index. On the other hand, the suburban areas have a low TOD-index. The statistical test showed that there was a strong correlation between different criteria. This paper concluded that most of the stations which were located in the suburban area had a low index thus need improvement. Consequently, the station areas needed to have a policy relevance.